Albania on the Move Links between Internal and International Migration - Vullnetari, Julie (IMISCOE Research, 2012)
This remarkable work is an academic and personal journey into Albania's post-communist society, examining the links between internal and international migration in one of Europe's poorest countries. Starting from a cluster of villages in south-east Albania, the author follows rural migrants to their native urban destinations within the country, such as Korçë and Tirana, as well as abroad to Thessaloniki, Greece. Migrants' lives, experiences and feelings are captured through 150 in-depth interviews, a number of group discussions and ethnographic observations. This rich empirical material is analysed with reference to an extensive body of literature in Albania and worldwide. The author's own experience as a migrant and reflections as a researcher studying her own origin communities add valuable insights. The theoretical notion of intra- and transnational social fields demonstrates how complex the links between internal and international migration are, especially from a development perspective, highlighting their effect on the lives of migrants, their families, communities of origin and country.